2018
DOI: 10.1161/strokeaha.117.018637
|View full text |Cite
|
Sign up to set email alerts
|

Role of Myeloid Lineage Cell Autophagy in Ischemic Brain Injury

Abstract: These data suggest that the lack of myeloid cell autophagy aggravates secondary injury by augmenting and prolonging inflammation after ischemic stroke without affecting the initial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…A population-based retrospective cohort study revealed that 18% of patients with central nervous system (CNS) infections developed CMHs within one year after the initial infection, 47 times greater than non-CNS infection controls [34]. Infections complicating cerebrovascular accidents have been extensively investigated [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. However, the role of CMHs complicating infections [55][56][57][58], in particular, acute infections, has been poorly explored [34,[59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…A population-based retrospective cohort study revealed that 18% of patients with central nervous system (CNS) infections developed CMHs within one year after the initial infection, 47 times greater than non-CNS infection controls [34]. Infections complicating cerebrovascular accidents have been extensively investigated [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. However, the role of CMHs complicating infections [55][56][57][58], in particular, acute infections, has been poorly explored [34,[59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…However, the down-regulation of hsp60 observed by the authors may not assess the occurrence of a pre-activation of autophagy by ischemic preconditioning, in order to boost further endogenous defense mechanisms [30]. Furthermore, although CRMP2 is particularly involved in autophagy, as it exerts a role in the efficient traffic of LC3-II containing autophagic vesicles, its involvement cannot be fully explained with the action exerted by quercetin on autophagy [21].…”
mentioning
confidence: 87%
“…We observed that the cross-talk between glial cells and neurons is of the utmost importance, during brain injury. A recent paper reported that in the ischemic stroke, inflammatory cells in the glia play a fundamental role in the exacerbation of ischemia causing neuronal cell apoptosis, if cells of myeloid lineage lack of an autophagic response [21]. Autophagy in this case has a protective role in preventing ischemia-induced damage of neuronal cells and interestingly quercetin, as many other polyphenols, is also an autophagy inducer [22].…”
mentioning
confidence: 99%
“…In response to an injury, the NLRP3 inflammasome can be regulated by autophagy, an intracellular homeostatic recycling process that eliminates damaged organelles and toxic agents, including inflammasomes [28]. Emerging research shows that autophagy modulates microglial inflammatory response via NLRP3 degradation [29], and autophagy impairment worsens neuroinflammation [30,31] and ischemic injury [32]. The pharmacological induction of autophagy inhibits inflammation and improves outcome in rodent models of cardiac arrest [33,34].…”
Section: Introductionmentioning
confidence: 99%